Analysis of the Interlock Spreader System for Lifting Containers on Rubber Tyred Gantry (RTG) - Hadi Arbi; Siti Anisah; Muhammad Erpandi Dalimunthe (Sean Institute, 2026)
Rubber Tyred Gantry is one of the heavy equipment used at container ports to carry out container loading and unloading activities. One of the main components of the RTG is the spreader, which functions to lift and lower the container through a twistlock system at all four corners. However, in practice, technical problems often arise such as the failure of the twistlock lock, which has the potential to pose a risk of work accidents and equipment damage. This study discusses the interlock system on the RTG spreader as a safety and control system in the container lifting process. The analysis was carried out through experiments by observing the electro-mechanical working system on the spreader seen directly in the field and simulating the logic of the interlock using Zelio Soft 2. If the twislock does not fit perfectly into the twislock hole, then the landed light does not turn on and the interlock process cannot be carried out. The landed light is on, so the container lock process can be done by the operator by pressing the lock button on the master control in the operator's cabin.And the lock process is complete, then the container is ready to be lifted. The interlock system is effective in preventing twistlock locking if the spreader has not been landed and hoist lifting if the lock process is not complete. The implementation of this interlock increases safety and effectiveness in the loading and unloading process at the Port and also requires regular maintenance of the landed sensor (proximity) as well as the adjustment of the distance of the landed sensor to the twis tlock pin needs to be carefully adjusted to prevent detection failure. By implementing this system, the level of work safety and operational efficiency of RTG can be significantly improved.